2018
DOI: 10.1039/c8ra03343a
|View full text |Cite
|
Sign up to set email alerts
|

Stability and local magnetic moment of bilayer graphene by intercalation: first principles study

Abstract: The migration and magnetic properties of the bilayer graphene with intercalation compounds (BGICs) with magnetic elements are theoretically investigated based on first principles study. Firstly, we find that BGICs with transition metals (Sc-Zn) generate distinct magnetic properties. The intercalation with most of the transition metal atoms (TMAs) gives rise to large magnetic moments from 1.0 to 4.0 m B , which is valuable for the spintronics. Moreover, graphene can protect the intrinsic properties of the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 68 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…These predictions are consistent with previous reports. 32,[47][48][49] The obtained total magnetic moments m tot and individual Mn atom magnetic moments m Mn provided in Table 1, clearly demonstrate that incorporation of the MnO x cluster in bilayer graphene is a suitable way to make it a magnetic material. Only the MnO 4 cluster-sandwiched graphene system displays nonmagnetic behavior.…”
Section: Resultsmentioning
confidence: 63%
“…These predictions are consistent with previous reports. 32,[47][48][49] The obtained total magnetic moments m tot and individual Mn atom magnetic moments m Mn provided in Table 1, clearly demonstrate that incorporation of the MnO x cluster in bilayer graphene is a suitable way to make it a magnetic material. Only the MnO 4 cluster-sandwiched graphene system displays nonmagnetic behavior.…”
Section: Resultsmentioning
confidence: 63%
“…Furthermore, here, the Dirac states are buried deep inside the valence band and the partially occupied 3d states occupy the Fermi level [35]. The same is observed when the 3d transition metals are intercalated [24,28]. The isolated vacancies create paramagnetic phase at low temperature with LSM arising due to the sublattice imbalance led zero mode π states and the re-hybridized σ dangling states [32,40].…”
Section: Introductionmentioning
confidence: 68%
“…While many such examples can be cited, the success is eluding when it comes to induce long range magnetic ordering in the graphene family. The effort in this direction so far had been either through semi-hydrogenation [4,5,[12][13][14][15][16], transition metal adatoms [17][18][19][20][21][22], and natural intercalations [23][24][25][26][27][28][29], vacancies [30][31][32][33][34][35], or through edge states in the flakes [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…Obtained results are consistent with earlier reports. 41,66,72,73 Fig. 3 illustrates the spin density of all the MnO x clusterintercalated bilayer AlN systems.…”
Section: Resultsmentioning
confidence: 99%
“…[32][33][34] Outcomes of these studies revealed that, foreign impurities when doped/intercalated into layered systems can easily alter the electronic, magnetic and optical parameters of layered 2D systems as compared to their pristine counterparts. Likewise, H. Jinsen et al 41 performed ab initio DFT calculations on TM atoms intercalated bilayer graphene and it was found that, TM intercalation in bilayer graphene can produce a stable 2D magnetic substrate. Few studies carried out on twisted/defective h-BN layers [42][43][44][45] suggest that, homo/hetero/defective layers can produce functional layered materials for nano-electronic and energy storage applications.…”
Section: Introductionmentioning
confidence: 99%